Best approach for addressing vacancies and unused space within Main Street districts - Linenberger, Raegan (Kansas State University, 2023)
Main Streets are known to be a vital part of smaller towns as they provide opportunity for investment and social connections, while also contributing to the city’s tax base and holding key parts of community identity. This makes it much more important to have Main Street districts that are functioning to their full potential which includes lowering vacancy numbers and finding ways to utilize unused space. This study employs a multiple case study approach to discover what has been done within other Main Street districts in Kansas to reduce the number of vacancies along their street front as well as utilize space that has been misspent. Information gathered from this case study investigation can then be applied to Main Street districts in need of guidance within these areas of Main Street development. The implication is that if Main Street districts are able and have the resources to resolve the issues of vacancies and underutilized spaces, then they will be less likely to fall into decline and will be able to provide more opportunity for economic and community development within their communities.
Keywords: Main Street; Vacancies; Unused space; Kansas; Kansas Main Street